Regenerative Surgical Therapy of Peri-implantitis: An Umbrella Review of Answered/Unanswered Questions and Future Perspectives - Solderer, Alex; Schmidlin, Patrick R. (Frontiers in Dental Medicine, 2020)
Purpose: To systemically summarize current knowledge about regeneration of peri-implant defects based on available systematic reviews. Materials and Methods: A systematic search for review articles published between 2010 and 2020 in four databases was conducted. Only systematic reviews and meta-analyses were included. Based on the available literature, five questions of clinical importance on indication for regenerative approaches, surgical technique, methods of decontamination, outcome of therapy and adjunctive use of biological factors were formulated and answered. Results: The electronic search resulted in 312 studies, from which 264 studies were published between 2010 and 2020. Finally, 18 systematic reviews and one consensus report were chosen. Data of the included studies were based on 58 to 840 implants. Data on over 4.904 implants were assessed. From the 19 studies that were included, 15 assessed the outcome of regenerative therapy; three, the surgical protocol of regenerative therapy; two, the use of laser in regenerative therapy; and one, the additional use of growth factors in regenerative peri-implant therapy. Three studies assessed more than one topic. Conclusions: In general, a partial bone fill can be expected in 85% of regenerative procedures. Regeneration leads to a mean of 57% of greater bone fill, compared to open flap surgery only. Defect configuration plays a crucial role in the outcome, whereas the role and extent of benefit of different surgical protocols are still not clear.